Spain as a multicultural and multilinguistic space. Languages in contact - Pawlikowska, Marta (Język(i) w czasie i przestrzeni, 2021)
The present article analyses the sociolinguistic situation in Spain in terms of minority, non-hegemonic languages in relation to Spanish. As the Constitution of this country points out, there are legal grounds for creating a de iure multilingual state, but if one delves into the issues, one can wonder whether one can speak here of multilingualism at all.